Numerical study of turbulent flow and heat transfer in a novel design of serpentine channel coupled with D-shaped jaggedness using hybrid nanofluid - Raditun E. Ratul; Farid Ahmed; Syed Alam; Md. Rezwanul Karim; Arafat A. Bhuiyan (Alexandria Engineering Journal, 2023)
This study aimed to examine numerically the effects of a dimpled surface over a mini-channel heat exchanger on the flow characteristics and heat transfer across a serpentine channel with a uniform rectangular cross-section. The dimples were arranged in parallel with a spanwise (y/d) distance of 3.125 and streamwise (x/d) distance of 11.25 along just one side of the serpentine channel's surface. Turbulent flow regime with Reynolds number ranging from 5 × 103 to 20 × 103 in the channel with the surface modification was studied using water and various volume concentrations (φ = 0.1%, 0.33%, 0.75%, 1%) of Al2O3-Cu/water hybrid nanofluid as the coolant to achieve a three-step passive heat transfer enhancement. Applying the Finite Volume Method (FVM), RNG k-e turbulence model, and a constant heat flux of 50 kW/m2, simulations were run assuming the mixture of Al2O3-Cu nanoparticles homogenous using ANSYS 2020 R1. The second-order upwind approach is used for approximation of solution and discretization with SIMPLE pressure–velocity coupling. Taking heat transfer increment and pressure drop penalty into consideration, the dimpled serpentine channel provides a 1.47-times improvement in thermal efficiency using water as the coolant, and the dimpled channel with 1% vol. Al2O3-Cu/water nanofluid enhanced thermal efficiency by a remarkable maximum of 2.67-times at Re 5 × 103. The study also indicates that thermal efficiency increased with an increasing volume concentration of the nanofluid and increment in thermal efficiency gradually decreased as the Re increased.